Time-Varying Risk Aversion? Evidence from Near-Miss Accidents - Shum, Matthew; Xin, Yi (The Review of Economics and Statistics, 2022)
We present evidence consistent with time-varying risk preferences among automobile drivers. Exploiting a unique data set of agents' high-frequency driving behavior collected by a mobile phone application, we show that drivers drive more conservatively following near-miss accidents. In a preferred specification, a near-miss triggers a reduction in driving distance of 12.98 kilometers, in-car cell phone use by more than 100%, and highway use by 43.24%. Structural estimation results indicate that such changes in behavior are consistent with an increase in risk aversion of 10.54% to 43.77% and a reduction in annual insurance cost amounting to 2.04% to 3.31% of the average car insurance premium.